Biogenerated silica nanoparticles synthesized from sticky, red, and brown rice husk ashes by a chemical method. Issue 4 (March 2016) - Sankar, S.; Sharma, Sanjeev K.; Kaur, Narinder; Lee, Byoungho; Kim, Deuk Young; Lee, Sejoon; Jung, Hyun
Abstract: An inexpensive chemical method was used to synthesize biogenic mesoporous silica (m-SiO2 ) from rice husk ash (RHA). A comparative study was carried out to produce silica nanoparticles (S-SiO2, R-SiO2, and B-SiO2 ) from three type of rice husk ashes (sticky, red, and brown). The microstructure of m-SiO2 was dependent on the geographical provenance and the types of RHA. An analysis of the SEM and TEM micrographs reveals that the S-SiO2 nanoparticles had a clustered spherical shape, while R-SiO2 and B-SiO2 nanoparticles were found to be purely spherical. The average crystallite size of S-SiO2, R-SiO2 and B-SiO2 nanoparticles evaluated from the TEM measurements were observed to be 50, 20 and 10 nm, respectively. The XRD pattern of silica nanopowders had an absence of sharp peaks that confirmed the amorphous nature of the material. The Fourier transform infrared (FTIR) spectra of silica nanoparticles showed the symmetric Si–O and O–Si–O stretching bond vibrations at 462, 1088, and 1098 cm −1 . The surface area of S-SiO2, R-SiO2 and B-SiO2 nanopowders was measured to be 7.5513, 201.45, and 247.18 m 2  g −1, respectively. The surface area of uniformly-distributed spherical nanoparticles of B-SiO2 was observed the highest, which can be applied for the application of energy storage and drug delivery systems.